A Taxonomy and Analysis on Internet of Vehicles: Architectures, Protocols, and Challenges. (30th May 2022) - Seth, Ishita; Guleria, Kalpna; Panda, Surya Narayan; Anand, Divya; Alsubhi, Khalid; Aljahdali, Hani Moaiteq; Singh, Aman
Abstract : The accelerated evolution in computing and transmission automation of the Internet of Vehicles (IoV) has led to enormous research standards that attract many researchers and industries. This century of the Internet of Things (IoT) is propulsive to the routine vehicular ad hoc networks (VANETs) in the IoV. It has emerged as one of the major driving forces for innovations in the intelligent vehicular industry. The World Health Organization (WHO) report confirms that approximately 1.35 million people die because of accidents on the road every year. This requires considerable attention to incorporate more and more safety measures into the automobile industry. Intelligent transportation systems can help bridge the gap between the traditional and the intelligent automotive industry by connecting vehicle to vehicle (V2V) and vehicle to infrastructure (V2I), hence adding much safety in vehicular communication. This paper provides a comprehensive review of the Internet of Vehicles (IoV) which discusses the architectures of IoV including layer types, functions of layers, application area, and communication type supported. Further, it also provides an in-depth insight into state-of-the-art Medium Access Control (MAC) protocols and routing protocols used in IoV communication. The routing protocol comparative summarization considers important parameters which include communication types broadcast, unicast, cluster, multicast, forwarding strategy, recovery strategy, availability of map, and the type of environment urban or highway. The summarization of various protocols highlights strengths, research gaps, and application areas. Finally, the paper addresses various research challenges along with potential future enhancements for the IoV communication.